Tổng hợp và cấu trúc dãy hidrazon chứa vòng furoxan đi từ axit isoeugenoxiaxetic - Tuyết Lan, Hoàng Thị; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
A series of nine hydrazones has been synthesized by condensation of 2-methoxy-4-(3-methyl-2-oxide-1,2,5-oxadiazol-4-yl)phenoxyacetylhydrazine with aromatic aldehydes. The structure of compounds has been confirmed by IR, 1H NMR and 13C NMR.